2017
DOI: 10.1016/j.jpeds.2017.04.047
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Externalizing and Internalizing Behaviors in Preterm Children Admitted to a Neonatal Intensive Care Unit

Abstract: Objective To examine trajectories of internalizing and externalizing behavior problems of preterm children between 16 months and 6 years of age and predictors of trajectories, including gestational age, child dysregulation, maternal depression, socioeconomic status, and parenting. Study design This longitudinal study followed 148 children and their mothers from Neonatal Intensive Care Unit (NICU) discharge until age 6. Gestational ages ranged from 23–36 weeks. The study included assessment of maternal-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 46 publications
3
22
1
Order By: Relevance
“…In any case the effect of the three variables of Model 1 (gestational age, gender and maternal education) on behavior problems was low (4% or 5 % of variance explained). Therefore, our results are in line with other studies in which a significant effect of maternal education was found on externalizing (Schappin et al, 2018), or internalizing and total problems at 6 years of age (Cassiano et al, 2018;Gerstein et al, 2017;Santos et al, 2017;Rose et al, 1992;), with a similar percentage of variance explained (7%).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In any case the effect of the three variables of Model 1 (gestational age, gender and maternal education) on behavior problems was low (4% or 5 % of variance explained). Therefore, our results are in line with other studies in which a significant effect of maternal education was found on externalizing (Schappin et al, 2018), or internalizing and total problems at 6 years of age (Cassiano et al, 2018;Gerstein et al, 2017;Santos et al, 2017;Rose et al, 1992;), with a similar percentage of variance explained (7%).…”
Section: Discussionsupporting
confidence: 93%
“…Our results confirm that GA does not seem to have a predictive role on behavior problems (Arpi & Ferrari, 2013;Cassiano et al, 2016;Cassiano et al, 2017;Cassiano et al, 2018;Gerstein et al, 2017;Santos et al, 2017), while other factors seem to have a higher predictive effect on behavior problems than GA; gender however, has no predictive effect on behavior problems, which is in agreement with Loe, Heller & Chatav (2019) findings.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Premature birth interrupts this structural development, which then becomes dependent on the care of a neonatal intensive care unit (NICU) [ 1 , 2 ]. Despite the fact that the NICU provides essential life support for the newborn, internal organic factors and intense exposures may affect the trajectory of its development [ 3 , 4 ]. The longer the NICU stay, the greater the benefit and recovery of neuromotor and cognitive functions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%